Tapak Suci as a Medium of Muhammadiyah Da’wah: A Qualitative Study of Branch 01 Limau Kebayoran Baru - Mohammad Haiqal An-Nur; Rika Sa'diyah (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This study aims to analyze the role of Tapak Suci Branch 01 Limau Kebayoran Baru as a medium of Muhammadiyah da’wah, the forms of da’wah implementation carried out within the organization, and the Islamic values embedded in its activities. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving administrators, trainers, and members of Tapak Suci. The data were analyzed using descriptive qualitative techniques through the processes of data collection, reduction, presentation, and conclusion drawing. The findings reveal that Tapak Suci Branch 01 Limau Kebayoran Baru functions not only as a martial arts organization but also as an effective medium of da’wah in fostering the younger generation through educational, character-building, and socio-religious activities. The implementation of da’wah is carried out through the Limau Ceria Mengaji Fastabiqulkhairat (LCMF) program and Amaliah Ramadhan activities, which contribute to improving religious understanding, strengthening Islamic character, and enhancing the involvement of members in Muhammadiyah da’wah activities. Furthermore, the activities of Tapak Suci embody various Islamic values, including faith and piety, noble character (akhlakul karimah), Islamic brotherhood (ukhuwah Islamiyah), discipline and responsibility, amar ma’ruf nahi munkar, leadership, and community service. These values are internalized through continuous training, exemplary leadership, habituation, and active participation in organizational activities. The study concludes that Tapak Suci successfully integrates physical, mental, social, and spiritual development, thereby contributing to the formation of cadres who are faithful, morally upright, socially responsible, and committed to supporting Muhammadiyah’s mission of da’wah and the development of a progressive Islamic society